PENCAPAIAN STANDAR PELAYANAN MINIMAL (SPM) PADA MADRASAH IBTIDAIYAH NEGERI (MIN) DI KOTA BANJARMASIN TAHUN 2014 - Ma'ruf, Hidayat (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2015)
Minimum Service Standards (Standar Pelayanan Minimal /SPM) is a measure of the performance of basic education services through formal education organized by District / City Government. SPM aims to create equitable quality of education, contains minimum provisions on what should be available and what should happen in the schools. SPM achievement study was conducted at 5 State Islamic Primary Schools in Banjarmasin. There are 2 formulations of research problems: 1) How is the SPM achievement of State Islamic Primary School / MIN in Banjarmasin in 2014 which is obligation for Banjarmasin government so far?; and 2) How is the SPM achievement of state Islamic primary school / MIN in Banjarmasin in 2014 which is an obligation for the education unit so far? This study is the evaluation, because the activities carried out are to compare the activities of a fact with the standards set out in the Regulation of the Minister of Education and Culture of the Republic of Indonesia No. 23 Year 2013. The results showed the average achievement of SPM at MIN in Banjarmasin 2014 which is the obligation of the government of Banjarmasin (MORA) is at 84% and 16% of SPM is not yet achieved. While the average achievement of SPM at MIN in Banjarmasin 2014 which is an obligation for the education unit (MIN) is at 76% and 24% SPM unmet.